2019
DOI: 10.1177/1077546319878976
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and vibration analysis of FG-CNT-reinforced composite rectangular thick nanoplates resting on Kerr foundation based on nonlocal strain gradient theory

Abstract: This paper investigates the buckling and free vibration analysis of functionally graded carbon nanotube-reinforced composite thick rectangular nanoplates resting on a Kerr foundation under different boundary conditions. Quasi-three-dimensional hyperbolic shear deformation theory is employed to study the effects of transverse shear deformation and thickness stretching. To capture the small-size effects of nanoscale dimensions, the nonlocal strain gradient theory is used, which includes nonlocal parameters and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Lu et al [52] developed a novel size-dependent model based on the NSGT in conjunction with the Gurtin-Murdoch surface elasticity theory to study the vibration behavior of FG cylindrical shells. With the help of quasi-3D hyperbolic SDT and NSGT, Shahraki et al [53] carried out a buckling and vibration analysis of thick rectangular FG carbon nanotubes reinforced composite (FG-CNTRC) nanoplates resting upon a Kerr foundation. Cutolo et al [54] applied a Reddy’s HSDT for the buckling and free vibration analysis of FGM nanoplates resting on a Winkler-Pasternak foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [52] developed a novel size-dependent model based on the NSGT in conjunction with the Gurtin-Murdoch surface elasticity theory to study the vibration behavior of FG cylindrical shells. With the help of quasi-3D hyperbolic SDT and NSGT, Shahraki et al [53] carried out a buckling and vibration analysis of thick rectangular FG carbon nanotubes reinforced composite (FG-CNTRC) nanoplates resting upon a Kerr foundation. Cutolo et al [54] applied a Reddy’s HSDT for the buckling and free vibration analysis of FGM nanoplates resting on a Winkler-Pasternak foundation.…”
Section: Introductionmentioning
confidence: 99%
“…where k s , k u , k l , refer to the shear layer, upper, and lower spring layers, respectively [39].…”
Section: Hamilton's Principle and Governing Equationsmentioning
confidence: 99%
“…From their study, it can be observed that the buckling behavior of clamped FGM nanoplates was very sensitive to various parameters such as aspect and side-to-thickness ratios, material graduation, thermal condition, etc. The study of the influence of small-scale parameters on the vibration and buckling behavior of CNT-reinforced FGM plates was done by Shahraki et al [ 31 ]. The CNT-based FGM nanoplate was considered to rest on a Kerr elastic foundation.…”
Section: Introductionmentioning
confidence: 99%